2009
DOI: 10.1242/jcs.050880
|View full text |Cite
|
Sign up to set email alerts
|

Troponin I and Tropomyosin regulate chromosomal stability and cell polarity

Abstract: doi:10.1242/jcs.05088

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 52 publications
(52 reference statements)
2
49
0
1
Order By: Relevance
“…In the absence of TnI, an inhibitory component within the troponin-complex proteins, the unregulated actomyosin interactions cause hypercontraction of the IFMs and TDT during early myofibrillogenesis (Nongthomba et al 2004). Using the UH3-Gal4 line, we attempted to rescue the hdp 3 allele with a nonflight muscle isoform of TnI, TnI-L9 (embryonic isoform) (Sahota et al 2009), to study the importance of isoform switching. Since, the driver UH3-Gal4 and the mutant allele hdp 3 are located on the X chromosome, we first recombined both alleles into a single chromosome and confirmed the muscle phenotype (figure 4b), which retained the hdp 3 phenotype.…”
Section: Embryonic Isoform Of Tni Rescues Myofibril Structure Of Nullmentioning
confidence: 99%
“…In the absence of TnI, an inhibitory component within the troponin-complex proteins, the unregulated actomyosin interactions cause hypercontraction of the IFMs and TDT during early myofibrillogenesis (Nongthomba et al 2004). Using the UH3-Gal4 line, we attempted to rescue the hdp 3 allele with a nonflight muscle isoform of TnI, TnI-L9 (embryonic isoform) (Sahota et al 2009), to study the importance of isoform switching. Since, the driver UH3-Gal4 and the mutant allele hdp 3 are located on the X chromosome, we first recombined both alleles into a single chromosome and confirmed the muscle phenotype (figure 4b), which retained the hdp 3 phenotype.…”
Section: Embryonic Isoform Of Tni Rescues Myofibril Structure Of Nullmentioning
confidence: 99%
“…As TnT3, TnT1, and TnT2 exhibit a classical LZD (Vinson et al ., 1989), TnT1 and TnT2 may have a nuclear function similar to that described for TnT3 in the present study. TnI has been reported in the nucleus of Drosophila nonmuscle cells (Sahota et al ., 2009) and TnI and TnT in rat and human cardiomyocytes (Asumda & Chase, 2012); however, their function in these locations is largely unknown. We consistently demonstrated that the nonmyofilament‐associated fast skeletal muscle TnT3 enters the nucleus through a COOH‐terminus nuclear localization sequence (NLS), KLKRQK (Zhang et al ., 2013a).…”
Section: Discussionmentioning
confidence: 99%
“…However, recently, expression of troponin in mouse vascular smooth muscle has been reported (Moran et al, 2008), although its function is still unclear. Furthermore, TNI is involved in the regulation of chromosomal stability and cell polarity in early Drosophila embryos (Sahota et al, 2009). Thus, additional cell-biological and genetic investigation on troponin in non-striated muscle and non-muscle cells might reveal unknown functions of the troponin complex or individual troponin components.…”
Section: (Rnai)mentioning
confidence: 99%